Kamble in a New Horizon: The Prisons we Broke as a Bildungsroman Genre - et. al., P. Revathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Prisons We Broke, in a sense, aids us to comprehend the ethos of Dalit communal and the vast vicissitudes that happened in due course of the period. Kamble, in her autobiography, resounds the impression of how women grieve from various dominations. She beautifully interlaces the triple domination that a Dalit woman undergoes in the name of gender, class and caste. Deplorably in a country like India, the caste decides the status of people. In style, Kamble, in her autobiography, depicts the incisive copy of the existing oppressive caste system, social stratum and patriarchal faith of the Indian society. Kamble's writing, in many ways, has helped to bring out her feelings and corporeal belligerences that a woman undergoes in the public and private sphere. Her autobiography has shared the most discrete reminiscences of her life, registering numerous astringent experiences at various phases to build up a narrative in a framework of the bildungsroman genre. This paper examines the methodology of how Baby Kamble has used her pen to convalesce the oppressed and endeavour for the improvement of Dalit women.